EFFECT OF SUGARCANE BY-PRODUCT BASED COMPLETE RATIONS ON NUTRIENT UTLIZATION AND MILK PRODUCTION IN MURRAH BUFFALOES* - R, PRASANNA KUMAR; K., SIVAIAH; E, RAGHAVA RAO (Indian Journal of Animal Production and Management, 2017)
Seven rations (six complete rations were formulated by using sugarcane byproductsand other crop residues and balanced concentrate mixture in the mash formand one conventional ration comprised with hybrid Napier and concentrate mixture)were prepared and fed to 28 Murrah buffaloes for a period of 180 days usingRandomized Block Design to study the effect of processing of complete diet on nutrientutilization and milk production. The DMI (kg/100kgbody wt) was significantly (P